Comparison of Laparoscopic vs Open Cholecystectomy in Acute Cholecystitis Presenting within 5 days of Onset of Symptoms - Murtaza, Mudassar; Ali, Mumtaz; Khalid, Warda; Javed, Aslam; Ahmad, Guled (Journal of Liaquat University of Medical & Health Sciences, 2024)
OBJECTIVE: To compare the result of open and laparoscopic cholecystectomy in managing acute cholecystitis presenting within 5 days. METHODOLOGY: This prospective comparative study was conducted at Government Teaching Hospital Shahdara Lahore from December 2020 to March 2023. Eighty patients with acute cholecystitis of 5 days or less duration and age >20 years were included and allocated into two groups, 40 in each. Non-probability convenient sampling was used. Group O was treated with open cholecystectomy, and Group L was treated with Laparoscopic cholecystectomy. Patients with empyema, common duct stones, liver failure and ASA grade >3 were excluded. Demographic data, operative time, complications, conversion rate to open surgery, hospital stay, and follow-up were recorded in proforma. Data entry and analysis were done using SPSS 24. RESULTS: Group O and Group L's mean age was 43.27±13.33 and 44.07±12.77 years, respectively. Gender distribution differed between Group O (5 males, 35 females) and Group L (8 males, 32 females). Hospital stay was significantly more extended in Group O (5.15±0.92 days) compared to Group L (2.67±0.72 days), with a significant difference in mean operative time (Group O: 75.20mins, Group L: 60.15mins). Wound infection rates were higher in Group O (3 patients) than in Group L (1 patient), and 2 out of 40 patients in the laparoscopic group required conversion to open surgery. CONCLUSION: Cholecystectomy, whether laparoscopic or open, is safe within 5 days of onset of acute cholecystitis with some benefit in laparoscopic surgery in terms of length of stay and recovery.